Houses in the Woods: Lessons from the Plum Creek Concept Plan - Bell, Kathleen (Maine Policy Review, 2007)
Residential growth pressures have arrived at the edge of Maine’s North Woods. Kathleen Bell in this article examines changes in the economics of rural land use in Maine. She notes that public debate over Plum Creek’s proposal for development in the Moosehead region reminds us that we need to increase our understanding of the interactions between residential growth pressures, changing landownership patterns, and new expectations for Maine’s forestlands
Keywords: Maine North Woods; Plum Creek; land use planning